2018
DOI: 10.1016/j.toxrep.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Orientin, a flavanoid, mitigates 1, 2 dimethylhydrazine-induced colorectal lesions in Wistar rats fed a high-fat diet

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
3
10
0
Order By: Relevance
“…In the current study, the growth rate was observed to be decreased in DMH/HFD rats when compared with control rats matching with Darband et al study [35]. This may be a consequence of higher tumor incidence, loss of appetite along with an increase in cachexia and anorexia [36,37]. Tenofovir-50 treatment did show an improvement in the colon architecture and tumor incidence; however, it lacked a marked effect on the growth rate compared with DMH/HFD group which was parallel to the reduction of food consumption.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, the growth rate was observed to be decreased in DMH/HFD rats when compared with control rats matching with Darband et al study [35]. This may be a consequence of higher tumor incidence, loss of appetite along with an increase in cachexia and anorexia [36,37]. Tenofovir-50 treatment did show an improvement in the colon architecture and tumor incidence; however, it lacked a marked effect on the growth rate compared with DMH/HFD group which was parallel to the reduction of food consumption.…”
Section: Discussionsupporting
confidence: 82%
“…In vivo, orientin administration (10 mg/kg) resulted in antiproliferative effects on 1,2-dimethyl hydrazine (DMH)-induced colorectal cancer in rats, and improved tumor marker levels while decreasing proliferative marker levels, such as proliferating cell nuclear antigen (PCNA) and Ki67 [396]. Orientin also reduced the occurrence of colonic polyps and aberrant crypt foci and increased the antioxidant defense in rats with DMH-induced colorectal cancer, demonstrating its antiproliferative and antioxidant properties in vivo [397].…”
Section: Orientinmentioning
confidence: 97%
“…Improved tumor marker levels and decreased proliferative marker levels [396]. Reduced occurrence of polyps and aberrant crypt foci [397]. Increased antioxidant defense [397].…”
Section: Orientinmentioning
confidence: 99%
“…Previously reported SrtA inhibitors include natural products [9,[16][17][18], synthetic products [19,20], and designed peptidomimetic compounds [21,22]. Orientin, a flavonoid isolated from various medicinal plants, is widely used in medicine because of its antiinflammatory, antioxidant, and antitumor effects [23][24][25][26]. In this study, we observed that it was an effective inhibitor of SrtA.…”
Section: Introductionmentioning
confidence: 71%